Analisis kebijakan bantuan internasional bencana alam dalam dinamika ketahanan nasional dengan pendekatan Delphi - Rawie, Yasserina; Rofii, M. Syaroni (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This study uses the Delphi method to analyze the strengths, weaknesses, opportunities, and threats of receiving international assistance for natural disasters in a country against the dynamics of national resilience. The Delphi method is one of the techniques used in mixed methods approaches. The researcher carried out several stages, from in-depth interviews, compiling variables for the questionnaire, and calculating the questionnaire result data to answer the research questions. The analysis will elaborate on several factors in national resilience: economy, politics, ideology, socio-culture, and defense and security. Based on the research results, four factors need to be taken into account by the government in responding to international natural disaster assistance: the type and scale of the disaster, assistance, the origin of the donor country, and the motives or interests of the donor country. It is advisable for the government to formulate policies related to its attitude to accept or reject international aid for natural disasters based on several possible conditions.